AB0410 Diagnosis of lung disease associated with rheumatoid arthritis, a prospective monocentric study. (12th June 2018) - Huber Somme, V.; Hirschi, S.; Ohana, M.; Felten, R.; Chatelus, E.; Javier, R.-M.; Sordet, C.; Arnaud, L.; Sibilia, J.; Gottenberg, J.-E.; Petit, H.
Abstract : Background: Respiratory involvement in rheumatoid arthritis (RA) is the most common extra-articular localisation, affecting 50% of patients, even though only 5% become symptomatic. Lung pathology as RA related interstitial lung disease is associated with significant morbidity and mortality. Involvement of the respiratory system seems frequent but remains underestimated because of the absence of guidelines about its detection in patients with RA. Objectives: This study aimed at determining the prevalence of respiratory involvement among symptomatic and asymptomatic patients with rheumatoid arthritis managed in a university hospital. Methods: We conducted a prospective observational study from May 2017 to January 2018 at the Strasbourg University Hospital. The patients included were over 18 years of age, had rheumatoid arthritis according to the ACR/EULAR 2010 criteria and signed informed consent. They responded to a self-administered questionnaire about their medical history, cardiorespiratory symptoms and lifestyle. Epidemiological, clinical and radiological data were assessed. All of the patients had a chest computed tomography (CT) and respiratory function tests (RFT). A collection of salivary flow and a test of Shirmer were carried out, to investigate the presence of a sicca syndrome. Chest CTs were interpreted by a radiologist specialised in lung area. Results: We included 102 successive patients, 73 women and 29 men. The average disease duration was 34 years. 60 patients were seropositive for rheumatoid factor and 68 for anti-CCP. 59 patients had bone erosions. The average disease activity score (DAS28-CRP) at inclusion was 3.5. 49 patients had associated Sjogren's syndrome. 22 were active smoker. 43 patients were taking long-term corticosteroid therapy. 96 patients were treated with conventional DMARD treatment, 28 with anti-TNF alpha therapy, 16 with Tocilizumab, 12 with Abatacept, 2 with JAK selective inhibitor, and 16 patients were under Rituximab. Of the 87 RFT performed, 39 were abnormal: 14 reported an obstructive syndrome, 8 a restrictive syndrome, 32 peripheral expiratory braking, suggestive sign of bronchiolitis, and 24 a decrease in the DLCO. Of the 91 chest CTs, 42 revealed lung nodules (42%), 15 of which were more than 6 mm; 29 interstitial syndrome (29%), among which 5 were non-specific interstitial pneumonitis (PINS), 3 common interstitial pneumonitis (PIC), and the other were non specific interstitial syndrome. 2 chest CT showed pleural effusion and 1 pericarditis. 44 patients had coronary calcifications, among whom 32 had no lipid-lowering therapy. Conclusions: Pulmonary systemic assessment of RA patients show high prevalence of respiratory involvement: 42% of patients had lung nodules and 29% had an interstitial syndrome. Detection of interstitial lung disease may raise questions about RA treatment such as anti-TNF alpha therapy. Rheumatologist should be more aware of respiratory involvement in RA patients and RFT, a non-invasive test, might be useful at diagnosis and follow-up. Disclosure of Interest: None declared